2002
DOI: 10.1093/nar/30.9.1869
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and recognition by DNA polymerases of a reactive nucleoside, 1-(2-deoxy-beta-D-erythro-pentofuranosyl)-imidazole-4-hydrazide

Abstract: We report the synthesis of a new nucleoside, 1-(2-deoxy-beta-D-erythro-pentofuranosyl)-imidazole-4-hydrazide (dY(NH2)) as a reactive monomer for DNA diversification. The 5'-triphosphate derivative (dY(NH2)TP, 1) was evaluated in vitro as a substrate for several DNA polymerases. Primer extension reactions showed that dYNH2TP was well tolerated by KF (exo(-)) and Vent (exo-) DNA polymerases. One dYNH2MP was incorporated opposite each canonical base with an efficiency depending on the template base (A approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…However, in the case of compounds 6-8, ZnCl 2 was added to increase the reactivity of the nucleoside phosphorimidazolides 10 and the compounds were purified by column chromatography followed by preparative HPLC to remove the EDTA-Zn 2+ complex. The ability of the phosphoramidate analogues (1)(2)(3)(4)(5) to function as substrate for HIV-1 RT was investigated by the gel-based single nucleotide incorporation assay (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of compounds 6-8, ZnCl 2 was added to increase the reactivity of the nucleoside phosphorimidazolides 10 and the compounds were purified by column chromatography followed by preparative HPLC to remove the EDTA-Zn 2+ complex. The ability of the phosphoramidate analogues (1)(2)(3)(4)(5) to function as substrate for HIV-1 RT was investigated by the gel-based single nucleotide incorporation assay (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these triphosphate mimics are obtained by modifying the bridging O-atoms of the triphosphate moiety 2 or using non-standard nucleobases. 3 In previous studies, we have demonstrated that the pyrophosphate moiety of nucleoside triphosphate can be replaced by leaving groups whose structures are not based on phosphate chemistry. For example, some selected amino acid derivatives could be considered as mimics of the pyrophosphate moiety of deoxyadenosine triphosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Next to immobilization, hydrazone formation-based methods are widely used for conjugating ONs and various reporter molecules, [4,10,12,19,27,28] including markers, dyes, and peptides. Most often 5'-modified ONs are obtained through post-synthetic introduction of the hydrazide function, and they were reported to be stable in solution.…”
Section: Introductionmentioning
confidence: 99%
“…For non-terminal modifications, the synthesis of a nucleoside analogue containing a hydrazide derived imidazole residue as a nucleobase was reported. [27] It can be incorporated into ONs both chemically and enzymatically. Conjugation with aldehydes permits the synthesis of a large variety of novel nucleobases in a single step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation